PS01.238: MESENTERY-ORIENTED LYMPH NODES DISSECTION AND INTRA-OPERATIVE NEURAL MONITORING TO REDUCE THE POSTOPERATIVE RECURRENT LARYNGEAL NERVE PARALYSIS IN ESOPHAGECTOMY. (14th September 2018) - Kobayashi, Hiroyuki; Mizumoto, Motoko; Kondo, Masato; Kita, Ryosuke; Masui, Hideyuki; Kitano, Shoichi; Kumata, Yukiko; Matsubara, Takaaki; Shiokawa, Keiichi; Kaihara, Satoshi; Hosotani, Ryo
Abstract: Description: Background: As the thoracic esophageal carcinoma has a high metastatic rate of upper mediastinal lymph nodes, especially along the recurrent laryngeal nerve (RLN), it is crucial to perform complete lymph nodes dissection along the RLN without complications. Although Intraoperative neural monitoring (IONM) during thyroid and parathyroid surgery has gained widespread acceptance as the useful tool of visual nerve identification, the utilization of IONM during esophageal surgery has not become common. Here, we describe our procedures focusing on a lymphadenectomy along the RLN utilizing the IONM. Methods and Procedures: We first dissect ventral and dorsal side of the esophagus preserving the membranous structure (mesoesophagus), which contains tracheoesophageal artery, RLN and lymph nodes. We next identify the location of the RLN which runs in the mesoesophagus using IONM before visual contact. After that, we perform lymphadenectomy around the RLN preserving the nerve. To evaluate the efficacy of this method, we compared short term surgical outcome of our 36 consecutive cases (neural monitoring group; Nm) of esophagectomy in prone positioning with 56 of our historical cases (conventional method group; Cm). Results: In all 36 cases of Nm group, we could obtain the location information of the RLN before the visual contact. Although the operation time of thoracic part was significantly longer in Nm group compared to Cm group (281 min vs. 254 min each, P  = 0.005), postoperative RLN paralysis according to postoperative laryngoscopy was seen in 3 cases (8.3%) after surgical operation in Nm group, which was significantly lower than that in the Cm group (18/56, 32.1%, P  = 0.005). As a result, median postoperative hospital stay was significantly shorter in Nm group than Cm group (22 days vs. 39 days each, P  = 0.0003). Conclusion: Mesentery-oriented lymph nodes dissection using IONM has substantial advantages to perform accurate and safe thoracoscopic esophagectomy. It could decrease the RLN paralysis and postoperative hospital stay after esophagectomy. Disclosure: All authors have declared no conflicts of interest.